IMPLEMENTATION OF ACADEMIC SUPERVISION AND SCHOOL CULTURE IN QUALITY OF EDUCATION : A SYSTEMATIC LITERATURE REVIEW - Ayun Fitroh Lutfiana; S. Nudia Mastur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The abstract The quality of education in educational institutions is felt to have not been maximized. Researchers are interested in examining how school culture and academic supervision are implemented and how they affect educational quality. The purpose of the study is to evaluate how well academic supervision functions within a company and how organizational culture affects educational quality. Increase the supervisors' understanding of leadership. An organized strategy of literature review was used in this investigation. locating data and information using Google Scholar, Mendeley, and journals. The findings indicated that the use of academic supervision and organizational culture in some studies had an impact on the enhancement of educational quality.